Aktivitas Antioksidan dan Profil Fitokimia Daun Kopi Kering Coffea arabica L. - Ni Luh Putu Ravi Cakswindryandani; Ryan Pieter I Nalle; Zainal Abidin; Yuliana Tandi Rubak (Itepa : Jurnal Ilmu dan Teknologi Pangan, 2026)
Arabica coffee is one of the mainstay commodities in the Manggarai region Nusa Tenggara Timur and has been widely known for its distinctive taste. Arabica coffee produced in the Manggarai region consists of three types, namely Manggarai arabica coffee, Yellow caturra coffee, and Juria coffee. While the utilization of Arabica coffee plants in Manggarai primarily focuses on coffee beans, other parts, such as leaves, have not been widely processed. Coffee leaves are rich in antioxidants, including phenols, flavonoids, saponins, tannins, and caffeine, which can provide functional benefits if processed. One potential use for coffee leaves is as an ingredient in herbal drinks. The drying process is crucial in herbal drink production as it affects the antioxidant and phytochemical content of coffee leaves. Therefore, this study aims to assess the antioxidant activity, antioxidant capacity, total phenolic content, tannin, and caffeine levels in dried coffee leaves from the three coffee variants for use in herbal drinks. Results showed that drying fresh of three variants of Manggarai arabica coffee in an oven at 60°C for 8 hours increased their antioxidant activity and capacity, as well as total phenol, tannin, and caffeine levels. The IC50 values (a measure of antioxidant activity) for Manggarai arabica coffee, Yellow caturra, and Juria dried leaves were 1121.43 ppm, 1423.66 ppm, and 1798.12 ppm, respectively. These results indicate that while processing fresh coffee leaves enhances their antioxidant activity, Manggarai coffee leaves exhibit weak antioxidant activity. Furthermore, the different coffee leaves variants did not significantly affect (P > 0.05) antioxidant activity, antioxidant capacity, or total phenolic content in dried coffee leaves. However, the tannin and caffeine levels in dried Manggarai arabica coffee leaves were significantly different (P < 0.05) compared to those in dried Juria coffee leaves.